Pengaruh Tegangan dan Bentuk Geometri Flywheel terhadap Energi Kinetik pada Motor Starter dan Massa Tetap Flywheel - Ravi Fadila Hafis; Wirawan Wirawan (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Flywheel is an important element in the motor starter system due to its ability to store relase kinetic energy during the rotation process. This study aims to evaluate the effect of rotation speed variation and flywheel geometry shape on the kinetic energy produced, assuming the flywheel mass is fixed. The analysis is conducted through theoretical approach and numerical simulation using the rotational kinetic energy equation, with I as the moment of inertia that depends on the geometry shape,and as the angular velocity and shape of  the flywheel. The results show that the geometry shape greatly affects the moment of inertia, and at the same angular velocity, the flywheel with larger moment of inertia is able to store more kinetic energy. The conclusion of this study provides recommendations in the selection of the optimal flywheel design to improve the efficiency of the motor starter system.